Numerical investigation of centrifugal compressor stability enhancement using vaned diffuser endwall contouring technology. Issue 8 (26th April 2022) - Cui, Qin; Qin, Guoliang; Jia, Cheng; Wang, Yi; Lei, Jian
Abstract: To improve the stable operating range of centrifugal compressor stage, endwall contouring technology is introduced on the hub‐side wall of the vaned diffuser for NASA CC3 centrifugal compressor as a promising technique to redistribute the flow field near the endwall in this paper. The main contents of this paper are listed as follows. First, a specific parameterized endwall contouring guideline is developed based on sinusoidal function and Bézier curve, and three factors are considered, namely, peak height, peak radial position, and frequency coefficient. Then, centrifugal compressor stages with baseline diffuser and contoured endwall diffusers are numerically investigated to reveal the influence of endwall contouring on the stable operating range. Results show that endwall contouring is an effective method to achieve stability enhancement with no evident reduction in stage performance on the design point. CEW13‐12 has the most successful combination of endwall contouring parameters, and stall margin is increased by up to 40% for CEW13‐12. Finally, the influence mechanism of endwall contouring on the stable operating range is discussed. At the near stall condition, the contouring endwall forces the fluid within the semi vaneless space to deflect toward the suction side to increase the momentum of low‐energy fluid in the suction surface boundary layer and reduce the adverse pressure gradient on the suction side, which delay the development of flow separation on the vane leading edge near the shroud side to suppress the onset of rotating stall. At the near choke condition, the contouring endwall has more potential to increase the throat area, resulting in a decrease of throat blockage to improve choke margin. The results show that the endwall contouring technology is a reliable method to achieve stability enhancement of centrifugal compressor stage. Abstract : Endwall contouring technology is an effective method to improve compressor stability. The most successful endwall contouring diffuser can improve the stall margin by up to 40%. Endwall contouring improves the ability to overcome the adverse static pressure gradient for the fluid to delay the onset of rotating stall.